DS11960558, A Water Soluble Prodrug of DS-2969b, for Intravenous Treatment of Clostridium difficile Infection. (4th October 2017) - Yamada, Makiko; Uchiyama, Minoru; Inoue, Shin-Ichi; Deguchi, Tsuneo; Furuta, Yoshitake; Yabe, Koichi; Masuda, Nobuhisa
Abstract: Background: Clostridium difficile infection (CDI) is the most common cause of diarrhea in hospitals. The only available intravenous (IV) therapy for CDI is metronidazole, which showed only a 52.4% cure rate in a prospective observational study. DS11960558 is a water-soluble prodrug of DS-2969b, which is a novel GyrB inhibitor in clinical development for oral treatment of CDI and has been found to be safe and tolerable in its phase 1 study. The in vivo efficacy and physicochemical, pharmacokinetic, and toxicological profiles of the prodrug were evaluated in this study. Methods: Efficacy was evaluated in a hamster CDI model. The animals were primed with a single subcutaneous (SC) clindamycin injection. Then, the infection was induced by oral gavage of C. difficile 2009155 (NAP1/027) spores. Treatment was initiated 6 hours post infection and repeated for 5 days. The animals were observed for survival and death once daily for 35 days. The physicochemical, pharmacokinetic, and toxicological profiles were evaluated by standard methods. Results: SC administration of the prodrug showed comparable and superior efficacy to oral (PO) administration of DS-2969b and the combination of metronidazole (SC) and vancomycin (PO), respectively, in the hamster CDI model (Figure 1). The solubility of DS-2969b was 0.4 mg/mL while that of the prodrug was much higher, >100 mg/mL. The prodrug was converted to DS-2969a (free form of DS-2969b) rapidly after IV administration, and the conversion ratio was >80% (Figure 2). The main metabolites in rat urine and feces were oxidized forms of DS-2969a, and there were no prodrug-specific metabolites. Fecal excretion of DS-2969a was similar between IV administration of the prodrug and PO administration of DS-2969b. Most of the radioactivity was recovered after IV administration of the 14 C-labeled prodrug in rats. The radioactivity was distributed widely in most tissues including the intestinal lumen, similar to the distribution of DS-2969b in rats. In safety pharmacology, genotoxicity, and rat 14-day repeated dose toxicity studies, the prodrug as well as DS-2969b did not show any significant findings. Conclusion: These results support development of DS11960558 as an alternative IV treatment option for CDI patients who cannot take medicine orally. Disclosures: M. Yamada, Daiichi Sankyo Co., Ltd.: Employee, Salary; M. Uchiyama, Daiichi Sankyo Co., Ltd.: Employee, Salary; S. I. Inoue, Daiichi Sankyo Co., Ltd.: Employee, Salary; T. Deguchi, Daiichi Sankyo Co., Ltd.: Employee, Salary; Y. Furuta, Daiichi Sankyo Co., Ltd.: Employee, Salary; K. Yabe, Daiichi Sankyo Co., Ltd.: Employee, Salary; N. Masuda, Daiichi Sankyo Co., Ltd.: Employee, Salary